The effects of MEX3A knockdown on proliferation, apoptosis and migration of osteosarcoma cells - Wang, Bangmin (Cancer Cell Int, 2021)
BACKGROUND: Osteosarcoma is an aggressive malignant tumor which has attracted worldwide attention. MEX3A may be associated with tumors while has not yet seen its coverage on osteosarcoma. Herein, this study was to investigate the correlation between MEX3A and the progression of osteosarcoma. METHODS: Firstly, we determined that expression of MEX3A was significantly higher in osteosarcoma tissues than that in marginal bone by immunohistochemical staining. Additionally, MEX3A expression was downregulated by the RNAi‐mediated knockdown. The functions of MEX3A knockdown on proliferation, apoptosis, cell cycle, migration was assessed by MTT assay, flow cytometry, wound-healing assay and Transwell assay, respectively. Knockdown of MEX3A resulted in suppressing cell proliferation, increasing cell apoptosis, inducing the G2 phase cell cycle arrest, and attenuating cellular migration. Furthermore, mouse xenograft model confirmed inhibitory effects of MEX3A knockdown on osteosarcoma formation. RESULTS: The preliminary exploration on the molecular mechanism of MEX3A in osteosarcoma cells showed that the induction of apoptosis needs the participation of a series of apoptosis- associated factors, such as upregulation of Caspase 3, Caspase 8 and HSP60, downregulation of HSP27 and XIAP. CONCLUSIONS: In summary, these findings predicated that therapy directed at decreasing MEX3A expression is a potential osteosarcoma treatment. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12935-021-01882-3.